Closing the gendered energy technology gap in rural Ethiopia: A qualitative study - Arega, Tiruwork; Yami, Mastewal; Bekele, Rahel Deribe; Ringler, Claudia; Jeuland, Marc (International Food Policy Research Institute, 2023)
Much has been written about energy poverty, but there is relatively limited evidence of what determines the gender gap in energy poverty and how it can be overcome in rural areas. This study used Focus Group Discussions, in-depth interviews with farmers and Key Informant Interviews to analyze gendered information, access, adoption and use of rural energy technologies in the domestic and productive spheres. We find striking differences in how men and women adopt and use energy technologies in both spheres. Substantial asymmetries exist between women and men regarding knowledge of energy technologies, as most information about them is directed to men in the household. Even so, women are typically the primary decision-makers regarding energy technology adoption for domestic use, while men dominate decision-processes in the productive energy technology space. Women remain largely excluded from the adoption and use of agricultural energy technologies, even though they are heavily engaged in agricultural production systems. Our study highlights the need for tailored mechanisms that reach women with information on and means to acquire energy technologies as well as changes in gendered norms to ensure that women benefit equally from their use.